Assessment of Heavy Metal in Imported Red Meat Available in the Markets of Erbil City (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Meat has comprised a significant part of the human diets worldwide. Nevertheless, pollution is a great health risk to human health, especially the bioaccumulation of heavy metals from anthropogenic. The study examined the concentrations of cobalt (Co), copper (Cu), iron (Fe), zinc (Zn), selenium (Se), nickel (Ni), mercury (Hg), lead (Pb) and arsenic (As) metals from imported meat of cattle, buffalo and lambs consumed in Erbil city by using X-ray fluorescence spectrometer. The estimate of essential metals investigated in meat samples indicates that meat from cattle, buffalo and lamb was found to have significantly higher levels of heavy metals and the concentration of these metals except for copper, iron, selenium and mercury in cattle and lambs exceeded the permissible limits set by international standard. Therefore, people of Erbil governorate that consume imported red meat such as cattle and lamb are likely to be exposed to higher metal levels.